Strength Of Evidence The Deed Under Of Hands In The Case Civil Evidence - Khalimah Khalimah; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Deed under the hand that has obtained the legalization give assurance to the judge about the date and the identity of the parties to the agreement. The strength of evidence deed under hand as evidence in court proceedings connected with the notary authority in legalization, as for the purpose of this research is to know how strong the deed under the hand of proof in proving the civil case.Research method used in this research is normative juridical study of the legal texts alone, but involves the ability of scientific analysis of legal materials to support eversafe against legal theory. Sources and Types of Data based on primary law material that is taken from the Book of Legislation applicable and secondary law, which consists of reference books and journals and scientific papers, the results of research related to materials research.From the research it can be concluded that the Power of the deed under the hand that had deilegalisasi by notary it would be perfect proof if the party wants and recognize the signature on the deed agreement under the hand that had terlegalisasi by Notary.Keywords: Legalization; Deed; Notary.